Friends in a field: conversations with raoul de keyser - Fogle, Douglas; Roosens, Ilse; Skerath, Hanneke; De Keyser, Raoul (New York : Gregory R. Miller & Co., 2023)
"Over the course of his nearly five-decade career, Belgian artist Raoul De Keyser (1930-2012) created paintings that bridge the mysteries of the everyday and the intangible world of abstraction. Friends in a Field: Conversations with Raoul De Keyser takes the artist's radical painterly practice as the beginning of a conversation with a diverse group of artists -- both living and dead -- whose works share a sensibility and attentiveness to the fragile intangibility of the world. In their paintings, sculptures and works on paper, these artists join De Keyser in presenting the world back to us as a kind of abstract visual poetry. Friends in a Field presents works by Richard Aldrich, Forrest Bess, Matt Connors, René Daniëls, Raoul De Keyser, Vincent Fecteau, Maysha Mohamedi, Rebecca Morris, Betty Parsons, Amy Sillman, Ricky Swallow, Patricia Treib, Luc Tuymans and Lesley Vance. Co-published with Mu.ZEE, Ostend"--
kunstcatalogus